ELICITATION TECHNIQUES IN QUESTIONING USED BY CONTENT AND LANGUAGE INTEGRATED LEARNING CLASSROOM TEACHERS - Islamiyah, Muflihah (2012)
This study aims to explore the elicitation techniques in questioning used by Content and Language Integrated Learning (CLIL) classroom teachers which focused on Science and Math subjects. This study was conducted on the basis of the fact that almost all classroom interactions during the teaching and learning process are built by questioning, in RSBI (Rintisan Sekolah Bertaraf International/Fledgling International Standard School) class in particular, with some ways of elicitations would always be used by the teachers. This study is a qualitative case study with four teachers who teach at SMP N 1 Margahayu as the participants. The data were collected by non-participant observation with video and audio recording, and interview. Analyzing data was done based on the transcription of observation and interview. Types of questioning from Kagan (1999) and elicitation from Tsui (in Coulthard, 2002) were used to analyze the data. The study shows that respondents produced skinny question more frequently than the other types of questions, followed by high-consensus question with 54.6% and 41% respectively. It indicates that the questions used were low level and needed convergent answer. However, there was also a result showing that the different methods of teaching would result with different question. Meanwhile, over half of elicit:inform was used by the teachers which reached 58.7% of all, followed by elicit:complete and elicit:agree with 21.8% and 7.5% respectively. This study revealed that the questions used by the teachers in CLIL classroom were posed by some elicitations which aimed to guide the students involved into the lesson. Keywords: Elicitation technique, elicitation in questioning, Content and Language Integrated Learning (CLIL)